2022
DOI: 10.3389/fnint.2022.899637
|View full text |Cite
|
Sign up to set email alerts
|

A Glitch in the Matrix: The Role of Extracellular Matrix Remodeling in Opioid Use Disorder

Abstract: Opioid use disorder (OUD) and deaths from drug overdoses have reached unprecedented levels. Given the enormous impact of the opioid crisis on public health, a more thorough, in-depth understanding of the consequences of opioids on the brain is required to develop novel interventions and pharmacological therapeutics. In the brain, the effects of opioids are far reaching, from genes to cells, synapses, circuits, and ultimately behavior. Accumulating evidence implicates a primary role for the extracellular matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 96 publications
1
11
0
Order By: Relevance
“…Considering that the AI is heavily weighted to prior behavior (i.e., before withdrawal), these results may indicate that the strongest ECM changes are state dependent and more specific to ongoing opioid use. These findings are consistent with previous reports that suggest that opioids induce various changes to ECM biology [reviewed in (35)], specifically, recent reports from human OUD patient that identified a key role for heroin-induced changes to ECM biology in promoting opioid use (15). Although ECM changes were most apparent from the AI and H24 conditions in this study, it is plausible that the processes affected by this remodeling may drive functional changes supporting relapse (37).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering that the AI is heavily weighted to prior behavior (i.e., before withdrawal), these results may indicate that the strongest ECM changes are state dependent and more specific to ongoing opioid use. These findings are consistent with previous reports that suggest that opioids induce various changes to ECM biology [reviewed in (35)], specifically, recent reports from human OUD patient that identified a key role for heroin-induced changes to ECM biology in promoting opioid use (15). Although ECM changes were most apparent from the AI and H24 conditions in this study, it is plausible that the processes affected by this remodeling may drive functional changes supporting relapse (37).…”
Section: Discussionsupporting
confidence: 93%
“…One major theme uncovered by these studies was heroininduced dysfunction in processes supporting ECM function throughout the reward circuit, which has been hypothesized to be a key component of substance use disorders (33)(34)(35)(36). The ECM of the brain is a complex milieu of proteins, proteoglycans, and polysaccharides that support various processes including cell-cell adhesion, blood-brain barrier integrity, and synaptic plasticity (20).…”
Section: Discussionmentioning
confidence: 99%
“…Using gene ontology analysis, we found that this hub gene cluster enriched for biological processes related to extracellular matrix (ECM) maintenance and associated collagen biology. This finding was particularly interesting given our recent work profiling transcriptional regulation in a mouse model of OUD, as well as recent findings in postmortem NAc from patients with OUD, both of which implicate an important role for ECM dysregulation in supporting opioid addiction pathology (11,12,30). Nearly all genes in this cluster were associated with module 3 (see sunburst plots in Figure 2), a large gene network containing nearly 5700 genes (Supp Fig 2B).…”
Section: Resultsmentioning
confidence: 70%
“…The top upregulated genes in dopamine neurons was the extracellular matrix protein Ecel1 , and the actin polymerization regulator Diaph3 , both of which are implicated in synaptic function and structural remodeling. These will be interesting gene targets to explore, as chronic morphine is known to induce structural plasticity of VTA dopamine neurons 12,38,39 , and extracellular matrix proteins are an area of interest in the opioid use disorder field 40 . We found increased expression of Insulin receptor substrate Irs1 and Irs2 , opposite of the decreased Irs proteins after chronic morphine in rat VTA 41 .…”
Section: Discussionmentioning
confidence: 99%